Levantamento metodológico de revisões sistemáticas de estudos de intervenção em periodontia utilizando AMSTAR 2 e ROBIS. - Alexandre Godinho Pereira (2022)
This study aimed to assess the methodological quality and risk of bias of systematic reviews and meta-analyses of intervention studies (randomized and nonrandomized studies) in periodontics. The following databases were searched: MedLine (PubMed), Embase (Elsevier), Web of Science, Scopus, Cochrane Library, and LILACS for systematic review articles, with or without meta-analysis, indexed between 2019 to 2020. Additionally, we searched on grey literature, and a manually searched the references of selected articles and main journals in the area. AMSTAR 2 and ROBIS tools were used to assess the methodological quality and risk of bias, respectively. Data were imported into the IBM SPSS Statistics for Windows version 25 software. Categorical variables were descriptively analyzed by relative and absolute frequency. Continuous variables were analyzed by mean, standard deviation, and minimum/maximum. One-hundred twenty-seven systematic reviews were included and were evaluated. In the overall ROBIS assessment, 113 (90.6%) were at high risk of bias, 11 (7.1%) were at low risk of bias, and 3 (2.4%) had unclear risk of bias. According to AMSTAR 2, 13 reviews (10.2%) had high methodological quality, 1 (0.8%) moderate, 31 (24.4%) low and 82 (64.6%) critically low. Overall, the quality of systematic reviews of intervention studies in the field of periodontics was low. Systematic review authors could use at least one between both tools before creating the study protocol. This simple process, if followed together with PRISMA, has the potential aid authors in the creation of more complete protocols and, consequently, better quality reviews.